Upaya Meningkatkan Minat Belajar PJOK Peserta Didik Menggunakan Pendekatan Etnopedagogi - Moch. Agus Salim; Anung Priambodo; Anggraini Ratna W (Departement of Mathematics Education, 2023)
This Research aims to increase the student interest of studying PJOK. The learning of PJOK which is used traditional the student of IV D grade in SDN Kemayoran I Surabaya for 2022-2023. Those students amount 34 students the kind of this research is include 2 (two) cyles. They are one cycle and two cyecle. Those cycles through planning step. Implementing the plan, observing the implementation and reflecting. This instrument which is used in this research is questionnaires. Those questionnaires have the students interest of studying PJOK, They are. Totally disagree, disagree, agree, totally agree indicators. The result of this research shows that the students interest of studying PJOK for IV D grade SDN Kemayoran I Surabaya in crease for 83,34%. In this case, it shows that the decrease of the student during the studying of PJOK. In the first cycle, there are 35,3% form 34 students who feel boring, sleepy and too tired. On the other hand. The second cycle, there are only 5,88% from 34 students who feel boring, sleepy and too tired. The result of this research also shows that the use of Etnopendagogi Approach can make the students better memorize and differ the type locomotor mation and non locomotor motion.